Randomized Pilot Study on the Effects of Sarcocornia as a Salt Substitute in Arterial Blood Pressure and Vascular Function in Healthy Young Adults - Telmo Pereira; Andreia Torres Caldeira; Armando Caseiro; Nádia Osório; Aida Moreira da Silva; Maria João Barroca (Foods, 2022)
Previous studies have shown that excessive salt intake is strongly associated with high blood pressure (HT), vascular dysfunction, and the overall risk of cardiovascular diseases. The aim of this study was to evaluate Sarcocornia effectiveness as a salt substitute, addressing its effect on cardiovascular function in healthy young individuals. Thirty healthy participants, aged 18 to 26 years, were randomized into two groups: the control group (CG) and the intervention group (IG). The IG used Sarcocornia powder as a salt substitute for cooking, and the CG used regular salt, during a period of 1 month. A baseline evaluation was performed before the participants started the intervention phase, and was repeated after a 30-day intervention period. Each evaluation included blood pressure (BP) measurement, carotid-femoral pulse wave velocity (PWV), and carotid pulse wave analysis (PWA), and blood samples were also collected for analysis. Sodium excretion was measured at baseline and after intervention through spot urine collection and analysis, a method suitable for this population but with known limitations. Baseline parameters were similar between groups and were within the normal range. Sodium excretion remained unchanged in the two evaluations in the CG, but significantly decreased after intervention in the IG. The reduction in sodium excretion in the IG was followed by a significant reduction in brachial and aortic systolic (SBP) and diastolic blood pressure (DBP), and also in PWV. No significant changes were observed in the CG in terms of cardiovascular parameters. This preliminary study conveys positive results in favor of Sarcocornia as a dietary substitute for regular salt, providing added evidence of the negative cardiovascular effects of high salt intake in young and healthy adults.